Effect of Mulch and Different Levels of N and K on the Growth and Yield of Onion (Progressive Agriculture, 2013)
An experiment was conducted to study the effect of mulch (non-mulch and straw mulch) and different levels of nitrogen (0, 40, 80 and 120 kg ha-1) and potassium (0, 37.5, 75 and 112.5 kg ha-1) on the growth and yield of onion. Plants grown with straw mulch gave higher bulb yield (10.89 t ha-1) which showed 13.79% increase over non-mulch. Nitrogen increased the bulb yield significantly.The highest nitrogen level gave the highest bulb yield (12.13 t ha-1), which was 41.54% increase over control. Potassium increased bulb yield compared to control, but its different levels had identical results on yield. Nitrogen and mulch together produced significant variations. The Nitrogen at the highest level (120 kg ha-1) along with straw mulch gave the highest yield (13.31 t ha-1). Potassium together with mulch also exhibited significant variation on yield and yield components. Plants grown with the highest level of potassium (112.5 kg ha-1) along with straw mulch gave the highest bulb yield (11.58 t ha-1). Nitrogen and potassium as 120 kg N ha-1 × 75.0 kg K ha-1 gave the highest bulb yield (13.07 t ha-1). Nitrogen and potassium at their maximum levels with straw mulch gave the highest bulb yield (14.67 t ha-1).DOI: http://dx.doi.org/10.3329/pa.v21i1-2.16747 Progress. Agric. 21(1 & 2): 39 - 46, 2010